1984
DOI: 10.1037/0021-9010.69.1.32
|View full text |Cite
|
Sign up to set email alerts
|

The power motive and managerial success in a professionally oriented service industry organization.

Abstract: This study examined the validity of McClelland's Leadership Motive Pattern (LMP) for two levels of management personnel in a professionally oriented, service industry organization Three types of outcome measures were used: attitudinal variables taken from survey responses of subordinates, objective measures of administrative performance taken from company records, and a variable representing the "importance"or "status" of the location in which the manager worked. Results indicated that, consistent with theory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1
1

Year Published

1986
1986
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 8 publications
1
30
1
1
Order By: Relevance
“…Although our total sample size (N=73) is substantially larger than typical sample sizes of previous studies using the motive coding methodology (e.g., see Cornelius & Lane, 1984, N=39;Spangler & House, 1991, N=39;Winter, 1987, N=34) and our subsample sizes (n=52 and n=21) are as large or larger than a previous study done by Cornelius and Lane (1984) under two levels of management personnel (n=21, n=18), the available samples are still relatively small. These small sample sizes are due to the amount of work involved in gaining access and conducting, transcribing, and coding the interviews, which is considerable.…”
Section: Study Limitationsmentioning
confidence: 91%
“…Although our total sample size (N=73) is substantially larger than typical sample sizes of previous studies using the motive coding methodology (e.g., see Cornelius & Lane, 1984, N=39;Spangler & House, 1991, N=39;Winter, 1987, N=34) and our subsample sizes (n=52 and n=21) are as large or larger than a previous study done by Cornelius and Lane (1984) under two levels of management personnel (n=21, n=18), the available samples are still relatively small. These small sample sizes are due to the amount of work involved in gaining access and conducting, transcribing, and coding the interviews, which is considerable.…”
Section: Study Limitationsmentioning
confidence: 91%
“…Individuals with high NACH tend to display entrepreneur behaviour and dislike bureaucracies. 60 High NACH individuals strive for employment in occupations or employment with organisations that have attractive images as a means to display their achievement. 61 In terms of SIT, this suggests that high NACH employees will seek employment in organisations with strong brand identities; however, since not all high NACH employees will fi nd employment with organisations possessing strong brand identities, we expect that perceived corporate brand identity will moderate the relationship between NACH and intent to remain with the organisation.…”
Section: Theoretical Development and Hypothesesmentioning
confidence: 99%
“…As is discussed later, McClelland and Burnham (1976) and McGIeIiand (1985) offered a theoretical rationale for the interplay between subconscious motives and cognitive expectancies and self-efficacies in determining effort. Further research has substantiated such claims (Cornelius & Lane, 1984;McClelland & Boyatzis, 1982).…”
mentioning
confidence: 80%
“…Current research sumests that patterns of motives may be better predictors of performanee in certain jobs rather than the motives done. For example, McCleiland and Boyatzis (1982), McCleiland and Burnham (1976), and Cornelius and Lane (1984) found that successful managers tend to be high on need for power and relatively low on need for affiliation and need for achievement.…”
Section: Motivationmentioning
confidence: 95%
See 1 more Smart Citation